Pengaruh Penyuluhan Partisipatif untuk Meningkatkan Pengetahuan Ibu tentang Penerapan Gizi Seimbang dalam Penanggulangan Stunting - Rohayati Rohayati; Aprina Aprina (Politeknik Kesehatan Tanjung Karang, 2021)
The incidence of stunting in Lampung increased from 3 (three) to 4 (four) out of 10 (ten) toddlers who experienced stunting. One way to overcome the high incidence of stunting is through counseling about balanced nutrition. The purpose of the study was to measure the effect of participatory counseling on the application of balanced nutrition to children under five on stunting prevention. This type of quantitative research with a Quasi-experimental research design was conducted in Panjang Bandar Lampung, from April to November 2020. The subjects were 60 mothers of children under five who were divided into the intervention group (30 people), and the control group (30 people). The research instrument used was a questionnaire and a knowledge test instrument, the intervention group received treatment in the form of participatory counseling while the control group only filled out the research instrument, namely a questionnaire. The previous data analysis was tested for normality by Shapiro Wilk then tested the data using the t-test. The results showed that there was an effect of participatory counseling in the application of balanced nutrition in increasing the knowledge of mothers of children under five (p-value=0,010). Participatory counseling was more effective in increasing knowledge about balanced nutrition compared to the control group (p-value=0,000). In conclusion, participatory counseling is significant in increasing mother's knowledge about balanced nutrition and has a better effect than other methods. Suggestion, one method of health promotion to overcome the problem of stunting is through participatory counseling.